1993
DOI: 10.1002/ajmg.1320470708
|View full text |Cite
|
Sign up to set email alerts
|

Variability of the Brachmann‐de Lange Syndrome

Abstract: Brachmann-de Lange syndrome (BDLS) is a relatively common multiple congenital anomaly/mental retardation syndrome, whose cause is unknown. The clinical variability of this condition is well-known. Recently some reports suggested the possible existence of a mild BDLS phenotype. We report on 30 patients in whom a diagnosis of BDLS was made or strongly suspected in 12 different Italian hospitals. Based on clinical evaluation we divided them into two groups, classical and mild BDLS cases. We compare the clinical d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 35 publications
(15 reference statements)
1
10
0
Order By: Relevance
“…One patient was missing the 2nd right toe. In previous surveys, major anomalies of lower limbs were represented in similar proportions and included mainly shortenings [Payne and Maeda, 1965; Ireland et al, 1993; Selicorni et al, 1993; Martinez‐Frias et al, 1998], while absence of a part of a lower limb was reported only occasionally (the absence of both tibiae, the right distal femur being bifurcated) [Pfeiffer and Correll, 1993].…”
Section: Discussionmentioning
confidence: 92%
“…One patient was missing the 2nd right toe. In previous surveys, major anomalies of lower limbs were represented in similar proportions and included mainly shortenings [Payne and Maeda, 1965; Ireland et al, 1993; Selicorni et al, 1993; Martinez‐Frias et al, 1998], while absence of a part of a lower limb was reported only occasionally (the absence of both tibiae, the right distal femur being bifurcated) [Pfeiffer and Correll, 1993].…”
Section: Discussionmentioning
confidence: 92%
“…Since the identification of the genetic etiology of CdLS, it has been appreciated that there is a wide range of severity in phenotypic features. The milder phenotype is characterized by a lower prevalence of major malformations, less distinctive facial features, and less significant psychomotor and growth delays [Ireland et al, 1993; Kline et al, 1993; Moeschler and Graham, 1993; Saul et al, 1993; Allanson et al, 1997; Selicorni et al, 2005]. …”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7] In an extensive review of 310 cases, Jackson et al 8 reported mildly affected cases to be more common than anticipated. Various behavioural phenotypes have been associated with CdLS, especially involving self injurious, 9 aggressive, and self restraining behaviour, and autism (-like) features.…”
mentioning
confidence: 97%